Meeting the Challenge - T. Reg Bott (International Journal of Chemical Engineering)
The first Chempor Conference held in Lisbon in 1975 under the auspices of the Calouste Gulbenkian Foundation, heralded a regular wide-ranging review of research and development in Portugal and the UK Progressively in later years the Conferences have attracted contributions from other European countries and indeed further afield. There is an increasing awareness of the problems for the environment, notably global warming, brought about by human activities. Recent predictions about the future are dire, particularly regarding food and water for a rapidly growing world population. They represent a substantial challenge to the scientific and technical fraternity. In response to that challenge it is important to keep up to date with technical developments, to meet and keep in touch with coworkers in associated fields, and to cooperate wherever possible. The papers presented at the Chempor and other conferences have made and continue to make a significant contribution to that objective of meeting the challenge.